2023
DOI: 10.1038/s41467-023-37711-6
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the complexity of spatiotemporal soliton molecules in real time

Abstract: Observing the dynamics of 3D soliton molecules can hold great opportunities for unveiling the mechanism of molecular complexity and other nonlinear problems. In spite of this fantastic potential, real-time visualization of their dynamics occurring on femtosecond-to-picosecond time scales is still challenging, particularly when high-spatiotemporal-resolution and long-term observation are required. In this work, we observe the real-time speckle-resolved spectral-temporal dynamics of 3D soliton molecules for a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In addition to single-pulse states, multi-pulse states, including harmonic mode-locking and bound states (or STDS molecules) 55 , 56 , 81 have been observed in MMF lasers. The multi-STDS spatiotemporal characteristics (e.g., pulse separation in a bound state) can be controlled by varying the lasing condition 55 , 56 , 109 , 124 , see Fig. 4 a. Spatially sampled autocorrelation measurements showed that temporal separations of the bound state are the same for pulses spatially sampled at different positions of the output beam, suggesting all the modal pulses are bounded with a uniform pulse separation 55 (Fig.…”
Section: Nonlinear Spatiotemporal Dissipative Soliton Dynamicsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition to single-pulse states, multi-pulse states, including harmonic mode-locking and bound states (or STDS molecules) 55 , 56 , 81 have been observed in MMF lasers. The multi-STDS spatiotemporal characteristics (e.g., pulse separation in a bound state) can be controlled by varying the lasing condition 55 , 56 , 109 , 124 , see Fig. 4 a. Spatially sampled autocorrelation measurements showed that temporal separations of the bound state are the same for pulses spatially sampled at different positions of the output beam, suggesting all the modal pulses are bounded with a uniform pulse separation 55 (Fig.…”
Section: Nonlinear Spatiotemporal Dissipative Soliton Dynamicsmentioning
confidence: 97%
“…The example shown in Fig. 3 c used speckle-resolved sampling and dispersive Fourier transform (DFT) technique 108 for real-time observation of spectral dynamics for STDSs 60 , 62 , 109 .…”
Section: Nonlinear Spatiotemporal Dissipative Soliton Dynamicsmentioning
confidence: 99%